Triple-Negative Breast Cancer Clinicopathology: A Single-Center Experience - Dedy Hermansyah; Yolanda Rahayu; Arjumardi Azrah; Gracia Pricilia; Sufida Sufida; Denny Rifsal; Albiner Simarmata (Indonesian Journal of Cancer, 2021)
Background: Triple-negative breast cancer (TNBC) is a subtype of breast cancer that does not have estrogen receptors, progesterone receptors, and HER-2 receptors. This subtype is found in 15-20% of all types of breast cancer, and it is often associated with a high recurrence rate and mortality after getting definitive therapy. The aim of our study is to investigate the clinicopathology of breast cancer in our center, where the majority were Bataknese.Methods: We evaluated the clinical and pathological characteristics of TNBC retrospectively from medical records data, from January 2017 to December 2019 with a total of 105 patients but only 79 patients had complete clinicopathological and immunohistochemistry data. This study was conducted in Murni Teguh Memorial Hospital, Medan, Indonesia. Results: From 79 TNBC patients, the average age at clinical presentation was 41-50 years group about 35 samples (44.3%). All patients had an invasive type of ductal carcinoma (100%). The majority of tumor size was T2 in 51 patients (64,6%), 83.6% grade 3 tumors. Both angioinvasion and lymph invasion were found in 48 patients (60.8%) while tumor-infiltrating lymphocyte (TIL) was found in 58 patients (73.4%), and 44 patients (55.7%) had lymph node metastases.Conclusions: According to some existing literature, TNBC showed more aggressive characteristics which are the same as our study. TNBC was diagnosed at young age, grade 3 tumors, having TIL which is very likely to occur distant metastases to lymph nodes.